Análise da amplitude do sinal eletromiográfico das porções do músculo quadríceps em protocolos de treinamento com diferentes durações das ações musculares - Gisele Freire da Silva (2016)
The aim of the present study was to analyze the EMG signal of VM, VL, and RF at strength training protocols with multiple series and similar duration of repetitions and different duration of muscle actions. Twelve female volunteers performed tree strength training protocols at the knee extension exercise with 3 series of 6 repetitions, 180 seconds between series and 50% of 1RM intensity, 6 seconds duration of repetition being configured in different ways for the 3 protocols: Protocol 1 1s of concentric action and 5s of eccentric action (1:5); Protocol 2 3s of concentric action and 3s of eccentric action (3:3); Protocol 3 5s of concentric action and 1s of eccentric action (5:1). It has been recorded the activation of vastus lateralis, vastus medialis and rectus femoris during the performance of strength training protocols and the root mean square of the electromyography normalized signal has been calculated for each repetition. It was also analyzed the activation ratios between VM/VL, VM/RF and VL/RF. Results showed that the muscle action durations performed resulted in different activation of VM and VL through the equivalent repetitions of each series, although similarly between protocols. The RF presented a different EMG profile for the three procedures (1:5, 3:3, 5:1). The protocols with different duration of muscle actions adopted in present study were able to change the ratio VM/VL and VL/RF only among some equivalent repetitions of each series. For VM/RF ratio no significant differences were observed. Thus, protocols with different durations of muscular actions seem to alter the EMG in a distinct way along the equivalent repetitions only for RF